A cluster randomized controlled trial of an after-school playground curriculum intervention to improve children's physical, social, and emotional health: study protocol for the PLAYground project - Allison Poulos; Pamela Hodges Kulinna (BMC, 2022)
Abstract Background The public health benefits of physical activity for children are well known including contributions to metabolic and cardiorespiratory health. Along with physical benefits, engaging in physical activity can support the social and emotional health of youth and promote health and well-being into adulthood. This cluster-randomized controlled trial assesses the impact of an after-school curriculum aimed at improving physically active and inclusive play to promote physical, social, and emotional health. A secondary focus is on the implementation (appropriateness, feasibility, fidelity, sustainability) of the curriculum. Methods The PLAYground (Play and Learning Activities for Youth) project utilizes a social-ecological approach, targeting personal, behavioral, and environmental conditions, and Social Cognitive Theory (SCT) to study how a playground curriculum impacts children's health. All elementary schools with an existing after-school program in a large, public school district in Mesa, Arizona will be eligible to participate. Seven schools will be allocated to the intervention arm in year one using random sampling stratified by school-income. In year two, the seven control schools will receive the intervention. Intervention schools will implement the research-based PlayOn!® playground curriculum to promote active and inclusive play. After-school staff will be trained to teach activities that address social and emotional skills (e.g., conflict resolution) through physical activity. Participating students will be trained as peer leaders to extend the playground activities to the recess setting. This trial will assess between-group differences in physical activity, social and emotional health indicators, and number of health and behavior incidents among students attending intervention schools and control schools. Implementation outcomes will also be assessed among program facilitators at each school site. Discussion Enhancement of physical activity opportunities at schools has the potential for high impact and reach due to practicality. Enhancements can also improve quality pedagogy and curricula in after-school settings. Results of this project can inform practical strategies to improve existing after-school programs to prepare leaders (adults and children) to facilitate physical activity, positive social interactions, and emotional well-being. Trial registration ClinicalTrials.gov, NCT ID NCT05470621 , Registered July 22, 2022,